2013
DOI: 10.1177/0300060513488504
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the clinical significance of FOXP3 protein expression in cervical oesophageal cancer and the number of FOXP3+ tumour-infiltrating lymphocytes

Abstract: Objectives: Investigations of FOXP3 protein expression in cervical oesophageal cancer cells and the number of FOXP3 þ lymphocytes infiltrating tumour tissue were undertaken. Methods: FOXP3 protein expression and FOXP3 þ tumour-infiltrating lymphocytes were studied immunohistochemically, in cervical oesophageal cancer tissue samples from 42 cases and paracancerous tissue samples from 30 of these cases. Results: The percentage of parenchymal cells expressing FOXP3 protein was significantly higher in cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Other investigators found Foxp3 expressed by human melanoma cells from fresh tissue and suggested that malignant transformation of healthy cells could induce Foxp3 expression [55]. More recently, Foxp3 protein expression was detected by immunohistochemistry and Western Blot in human parenchymal cells from cervical oesophageal cancer [56], gastric tumor cells [57] [58] and invasive ductal breast carcinoma [59]. Furthermore, expression of Foxp3 mRNA has been observed in several human cancer cell lines [60] and recently in the mouse B16F10 melanoma cell line [61].…”
Section: ) Foxp3 In Normal and Malignant Epithelial Cellsmentioning
confidence: 96%
“…Other investigators found Foxp3 expressed by human melanoma cells from fresh tissue and suggested that malignant transformation of healthy cells could induce Foxp3 expression [55]. More recently, Foxp3 protein expression was detected by immunohistochemistry and Western Blot in human parenchymal cells from cervical oesophageal cancer [56], gastric tumor cells [57] [58] and invasive ductal breast carcinoma [59]. Furthermore, expression of Foxp3 mRNA has been observed in several human cancer cell lines [60] and recently in the mouse B16F10 melanoma cell line [61].…”
Section: ) Foxp3 In Normal and Malignant Epithelial Cellsmentioning
confidence: 96%
“…Increased recruitment of Tregs in esophageal cancer, particularly ESCC, is at least partially mediated by the chemokines CCL17 and CCL22, which are secreted by tumor cells and macrophages to recruit Tregs via the CCR4 receptor 114 . Furthermore, Treg infiltration was found to have prognostic significance, with higher amounts of Tregs associated with deeper tumor invasion 115 , metastasis 116 , overall disease severity 117 , and decreased survival post-chemotherapy 118 . In addition, a recent report on esophageal cancer patients receiving neoadjuvant chemoradiation showed that the density of Tregs in the residual tumor (post-treatment) was correlated not only with pathological response but also with cancer-specific survival 119 .…”
Section: Immune Modulation Promotes Tumor Evasion and Survivalmentioning
confidence: 99%
“…T regs are often found at high frequencies in the peripheral blood and tumors of human patients compared with those in healthy donors and normal mucosa or tissue [93], and in many cancers, a high density of T regs correlates with poor disease outcomes [94]. In adoptive cellular immunotherapy in cancer, the functions of immune cells are always inhibited.…”
Section: Clinical Implications In Cancer Therapymentioning
confidence: 99%